2013
DOI: 10.7863/jum.2013.32.1.143
|View full text |Cite
|
Sign up to set email alerts
|

Needle Echogenicity in Sonographically Guided Regional Anesthesia

Abstract: This study shows that anesthesiologists prefer certain visual characteristics of needles used in sonographically guided regional anesthesia procedures. Specifically, needle tip clarity most closely predicted clinician needle preferences. These results support the idea that all echogenic needle designs do not uniformly enhance needle visualization. Further studies are needed to determine whether needles with superior tip clarity predict not only clinician preferences but also improved sonographically guided reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Taking a step forward, specific needle surface modifications allowing ultrasound reflection irrespective of angle of orientation have been recently developed in an attempt to enhance needle visualization in US for regional blocks [71421]. Sviggum et al [22] reported that the SonoPlex Stim needle (Pajunk Medical Systems, Tucker, GA, USA) was rated highest for brightness and clarity in a gel phantom compared to several echo-enhanced needles. The SonoPlex Stim uses contains a texturized needle surface with multiple flat, angled laser-based markings called 'Cornerstone' reflectors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Taking a step forward, specific needle surface modifications allowing ultrasound reflection irrespective of angle of orientation have been recently developed in an attempt to enhance needle visualization in US for regional blocks [71421]. Sviggum et al [22] reported that the SonoPlex Stim needle (Pajunk Medical Systems, Tucker, GA, USA) was rated highest for brightness and clarity in a gel phantom compared to several echo-enhanced needles. The SonoPlex Stim uses contains a texturized needle surface with multiple flat, angled laser-based markings called 'Cornerstone' reflectors.…”
Section: Discussionmentioning
confidence: 99%
“…These indented regions increase the surface area of the needle across which the waves are reflected. These indentations between the smooth surfaces cause intense waves reflecting at different angles to bounce back to the probe by changing the reflected angles of the waves coming from the transducer [71922]. Gofeld et al [23] also noted that SonoPlex Stim appeared to have better needle tip visibility in their human cadaveric study followed by EchoStim (Havel Inc., Cincinnati, OH, USA) among representative commercially available echogenic needles in the United States.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maintaining the needle in an orientation perpendicular to the ultrasound beam will ensure that the needle is echogenic and easily identifiable. Some manufacturers produce needles with specific design features that enhance their echogenicity; this may assist especially in deep-targeted injections or areas with limited access 34. Additionally, as ultrasound is a dynamic image, oscillating the needle gently while slowly scanning with the transducer can help to locate the needle tip in difficult situations 35 36…”
Section: Ultrasound-guided Injectionsmentioning
confidence: 99%
“…For the safety and success of a PLB, it is crucial that needle visibility and identification are optimal. These are also of importance in other procedures, such as those involving vascular access [ 7 , 8 ] or in ultrasound-guided regional anesthesia [ 5 ]. To overcome poor needle visibility, two solutions are available: the imaging techniques may be adjusted or the visibility of the needle itself may be improved by increasing its echogenicity, i.e., the ability to reflect the ultrasound signal.…”
Section: Introductionmentioning
confidence: 99%